NONDELEGATION AND CRIMINAL LAW - Hessick, F. Andrew; Hessick, Carissa Byrne (Virginia law review, 2021)
Although the Constitution confers the legislative power on Congress, Congress does not make most laws. Instead, Congress delegates the power to make laws to administrative agencies. The Supreme Court has adopted a permissive stance towards these delegations, placing essentially no limits on Congress's ability to delegate lawmaking power to agencies. In its recent decision, Gundy v. United States, the Court relied on this unrestrictive doctrine to uphold a statute delegating the power to write criminal laws. In doing so, the Court did not address whether greater restrictions should apply to delegations involving criminal law. Instead, it applied the same permissive test that it uses to evaluate other types of delegations. This Article argues that criminal delegations should be treated differently. A number of legal doctrines distinguish criminal laws from other laws. Examples include the vagueness doctrine, the rule of lenity, and the prohibition on criminal common law. The principles underlying these exceptional doctrines equally support tighter restrictions on criminal delegations. Moreover, the justifications in favor of permitting delegations apply less forcefully to criminal laws. Accordingly, this Article proposes that criminal law delegations be subject to greater restrictions than other delegations.